Development of Islamic-based interactive Powerpoint learning media on the material of many-sided flat buildings grade 4 Primary School - Iswahyuono, Akbar Alifian; Wahyuni, Indah; Farihah, Umi (SAINTIS Publishing, 2023)
Nowadays, the development of education is influenced by the rapid advancement of information and communication technology. One of them is affecting the development of learning media. The learning process can now be carried out by utilising various learning media, one of which is interactive powerpoint. The use of learning media to support the learning process needs to be developed in the education system. Learning media can be made using various applications, one of which is Microsoft Powerpoint. This research is included in the type of development research or commonly called RnD (Research and Development) by taking the ADDIE development model. The ADDIE development model includes five stages, namely analysis (Analysis), design (Design), development (Development), implementation (Implementation) and evaluation (Evaluation). From the five stages in the ADDIE model above, researchers only carry out up to the implementation stage, due to the lack of time so it is not possible to carry out all the stages. The interactive powerpoint learning media for mathematics on the material of flat faceted shapes has been successfully developed. With the acquisition of the percentage value of three expert validations classified as high at 92% and the acquisition of practicality tests from students showing very practical results of 93.3%, then based on these gains the learning media can be categorised as feasible for use in learning. Furthermore, it can be suggested to teachers and students to be able to utilise it as an alternative media in learning mathematics material of many-sided flat shapes.